The girl with braided hair [large type] - Coel, Margaret, 1937- (Coel, Margaret, 1937- Wind River mystery., 2008)
In 1973, Liz Plenty Horses was accused of betraying the militant American Indian Movement, known as AIM, to the FBI after the death of one of their members. She went into hiding with her baby daughter, never to be seen again. Now, a skeleton with a bullet hole in the back of the skull has been discovered at the bottom of a ravine on the Wind River Reservation. The body was that of a woman who was murdered sometime in 1973. With the police reluctant to investigate, Arapaho attorney Vicky Holden and Father John O'Malley must unravel the truth-even if it incites the malice of a long-dormant killer.